4x+13-6x=15-18x+16-2

Simple and best practice solution for 4x+13-6x=15-18x+16-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+13-6x=15-18x+16-2 equation:


Simplifying
4x + 13 + -6x = 15 + -18x + 16 + -2

Reorder the terms:
13 + 4x + -6x = 15 + -18x + 16 + -2

Combine like terms: 4x + -6x = -2x
13 + -2x = 15 + -18x + 16 + -2

Reorder the terms:
13 + -2x = 15 + 16 + -2 + -18x

Combine like terms: 15 + 16 = 31
13 + -2x = 31 + -2 + -18x

Combine like terms: 31 + -2 = 29
13 + -2x = 29 + -18x

Solving
13 + -2x = 29 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
13 + -2x + 18x = 29 + -18x + 18x

Combine like terms: -2x + 18x = 16x
13 + 16x = 29 + -18x + 18x

Combine like terms: -18x + 18x = 0
13 + 16x = 29 + 0
13 + 16x = 29

Add '-13' to each side of the equation.
13 + -13 + 16x = 29 + -13

Combine like terms: 13 + -13 = 0
0 + 16x = 29 + -13
16x = 29 + -13

Combine like terms: 29 + -13 = 16
16x = 16

Divide each side by '16'.
x = 1

Simplifying
x = 1

See similar equations:

| 10=2*3+2w | | (-4t^2)^2/2t | | 10+3x=2(3+4c)+5 | | 7-14y-18+9y= | | (1-y)dx-(1-x)dy=0 | | 80z^8-46z^6=0 | | 3(2x-3)-1=6x-10 | | 52=x+(2x-5) | | -6x^2+46x+52=0 | | 16x=-6 | | 5x+13+(-16x)= | | 4y-1+y+12=7y+20-5y | | 72p-2p^3=0 | | 4x^2+12x^2=45 | | 6r-3r+4=6r-r | | 4x+42=7x+9 | | 13x-12+18=180 | | 2(3+2x)-1=9 | | 3x+18y=180 | | -243=-8(10+x) | | 2(4x-3)-8=4-2x | | m/7=5m/15 | | 12.50+.4m=14.75+.25m | | w/5-10 | | 3(x+1)=6+3x | | 6y+9-7= | | 14x^2+36x=38.75 | | 20x+31=9x | | 3w^2=8w+20 | | 4(3+3x)-3=70 | | 5x+12y=2x^2 | | -4x+31.5=-65.1 |

Equations solver categories